Analysis of Soft Selling Through Scarlett Whitening's Product Placement in the Korean Drama "Reborn Rich" on Purchase Intention (Survey on Instagram Followers @hallyu.smi) - Nazhira Nur Pasha; Tetty Sufianty Zafar; Kokom Komariah (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study aims to analyze the effect of soft selling through product placement Scarlett Whitening in the Korean drama “Reborn Rich” on purchase intention on Instagram followers @hallyu.smi. The phenomenon of the rise of Korean culture in Indonesia is utilized by various brands to carry out effective marketing strategies, one of which is through product placement in Korean dramas. The method used in this research is a quantitative approach with an associative research type. Data was collected through distributing questionnaires to 135 Instagram followers @hallyu.smi who have watched the Korean drama “Reborn Rich”. Data was obtained through a research questionnaire distributed containing 27 questions regarding soft selling variables, product placement variables and purchase intention variables. Furthermore, the data obtained will be carried out various tests such as validity and reliability tests using the help of smartPLS 3.0 software. The results showed that the soft selling variable on purchase intention, the product placement variable on purchase intention, the soft selling variable on product placement and the product placement variable mediated effectively in the relationship between the soft selling variable and the purchase intention variable.